The Seaside Cafe - Alers, Rochelle (Alers, Rochelle. Book club series, 2020)
"For three decades, the Seaside Café has served delicious meals to locals and island tourists alike. Kayana Johnson has moved home to help her brother run the café - and to nurse her wounds following a deep betrayal. Between cooking favorite recipes - creole chicken with buttermilk waffles, her grandmother's famous mac and cheese - and spending time reading, Kayana is trying to embrace a life free of entanglements, while staying open to new connections . . .After striking up conversation with two customers, Kayana suggests a summer book club. Each week, they'll meet on the patio to talk about their favorite novels. But there are plot twists awaiting them in real life too. For schoolteacher Leah, this two-month sojourn is the first taste of freedom she's had in her unhappy marriage. Cherie, filled with regret about her long-term affair with a married politician, discovers a powerful new passion. And Kayana finds a kindred spirit in a reclusive visitor who's ready to make his true identity known, and fill this summer with new possibilities . . ."--Publisher.